A catalogue of masses, structural parameters, and velocity dispersion profiles of 112 Milky Way globular clusters. Issue 2 (1st May 2018) - Baumgardt, H; Hilker, M
ABSTRACT: We have determined masses, stellar mass functions, and structural parameters of 112 Milky Way globular clusters by fitting a large set of N -body simulations to their velocity dispersion and surface density profiles. The velocity dispersion profiles were calculated based on a combination of more than 15000 high-precision radial velocities which we derived from archival ESO/VLT and Keck spectra together with ∼20000 published radial velocities from the literature. Our fits also include the stellar mass functions of the globular clusters, which are available for 47 clusters in our sample, allowing us to self-consistently take the effects of mass segregation and ongoing cluster dissolution into account. We confirm the strong correlation between the global mass functions of globular clusters and their relaxation times recently found by Sollima & Baumgardt (2017 ). We also find a correlation of the escape velocity from the centre of a globular cluster and the fraction of first generation stars (FG) in the cluster recently derived for 57 globular clusters by Milone et al. (2017 ), but no correlation between the FG star fraction and the global mass function of a globular cluster. This could indicate that the ability of a globular cluster to keep the wind ejecta from the polluting star(s) is the crucial parameter determining the presence and fraction of second-generation stars and not its later dynamical mass loss.